Identification of Candida species in the oral cavity of diabetic patients - Faezeh Mohammadi; Mohammad Reza Javaheri; Shahram Nekoeian; Parvin Dehghan (Mazandaran University of Medical Sciences, 2016)
Background and Purpose: Diabetic patients are more susceptible to oral candidiasis infection than non-diabetics due to the factors promoting oral carriage of Candida. Several factors can increase colonization of Candida species in the oral cavity such as xerostomia, which reduces the salivary flow and is a salivary pH disorder. In the current study, we aimed to identify and compare the colonization level of Candida spp. in the oral cavity of diabetic and non-diabetic groups. Materials and Methods: Swabs were taken from the mouth of 106 participants and were cultured on Sabouraud dextrose agar (SDA) medium. Likewise, the saliva samples were collected for salivary glucose and pH measurements. The study was performed during June 2014-September 2015 on two groups of diabetic patients (n=58) and non-diabetics (n=48) as the control group. The Candida spp. were identified with PCR-restriction fragment length polymorphism (RFLP) using the restriction enzymes HinfI and MspI and were differentiated by culture on CHROMagar Candida medium. Results:The frequency of Candida spp. was higher in diabetic patients compared to non-diabetics. The most frequent Candida spp. in the diabetic patients were Candida albicans (36.2%), C. krusei (10.4%), C. glabrata (5.1%), and C. tropcalis (3.4%). Likewise, C. albicans was the most frequent species (27%) in the non-diabetic individuals. In this study, the results of both methods for identification of the isolates were consistent with each other. Conclusion: Xerostomia and disturbance of physiological factors including pH and glucose can promote overgrowth of Candida flora in the oral cavity. These factors are considered important predisposing factors for oral candidiasis in diabetic patients. In the present study, it was observed that application of CHROMagar Candida and PCR-RFLP methods at the same time contributes to more accurate identification of isolates.